(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The edition of texts written in the ancient European languages (Palaeo-European) has been substantially conditioned by the progress of other disciplines that are narrowly linked to it and by the recent technological developments. This chapter describes the history of the scientific approach to Palaeo-European texts, that started as a purely textual analysis and is currently the result of a balanced interaction of every field. This historiographic panorama is structured in three phases: from its first steps in the 18-19th centuries until the first half of the 20th, the second half of the 20th century and, last, the first decades of the 21st. Finally, the contribution of the AELAW network is contextualized and some potential lines of research are suggested.